2021
DOI: 10.3389/fphys.2021.628819
|View full text |Cite
|
Sign up to set email alerts
|

The Energy of Muscle Contraction. III. Kinetic Energy During Cyclic Contractions

Abstract: During muscle contraction, chemical energy is converted to mechanical energy when ATP is hydrolysed during cross-bridge cycling. This mechanical energy is then distributed and stored in the tissue as the muscle deforms or is used to perform external work. We previously showed how energy is distributed through contracting muscle during fixed-end contractions; however, it is not clear how the distribution of tissue energy is altered by the kinetic energy of muscle mass during dynamic contractions. In this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…We ran simulations with the fully dynamic model on a muscle-aponeurosis configuration as in Figure 3, and subjected the +x-face of the top aponeurosis to cyclic contractions; simultaneously, the muscle fibres were activated in a synchronized manner. We found comparable patterns of tissue accelerations in the longitudinal direction across the dynamic model during cyclic contractions [64] to that of the experiments on rat plantaris muscle [67], again scaling the accelerations by a length scale corresponding to the location in the muscle. We found a larger difference in scaled acceleration in the middle of the muscle relative to the end with greater muscle size for the model and greater added mass for the in situ muscle.…”
Section: Validation Of Modelssupporting
confidence: 71%
See 2 more Smart Citations
“…We ran simulations with the fully dynamic model on a muscle-aponeurosis configuration as in Figure 3, and subjected the +x-face of the top aponeurosis to cyclic contractions; simultaneously, the muscle fibres were activated in a synchronized manner. We found comparable patterns of tissue accelerations in the longitudinal direction across the dynamic model during cyclic contractions [64] to that of the experiments on rat plantaris muscle [67], again scaling the accelerations by a length scale corresponding to the location in the muscle. We found a larger difference in scaled acceleration in the middle of the muscle relative to the end with greater muscle size for the model and greater added mass for the in situ muscle.…”
Section: Validation Of Modelssupporting
confidence: 71%
“…In Figure 4, we present time traces of the x-components of the displacement. These are measured at 4 distinct points along the centerline of the muscle block: at x(L) (the face being pulled), x 1 close to this face, x mid at the midpoint of the block and x 2 close to the clamped and the simplified version of the medium gastrocnemius from [64] (bottom). Note that in the block geometry, the fibres run parallel to the x-axis, whereas in the medium gastrocnemius they run at an angle θ 0 from the x-axis.…”
Section: Dynamic Muscle Mechanicsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously found smaller reductions in mass-specific mechanical work due to greater mass in muscles with higher fibre pennation angles at rest [64]. If we assume that pennation angle has little effect on metabolic cost, which may be reasonable given how little muscle mass altered metabolic cost in this study, muscles with higher pennations may be more efficient for larger muscles in larger animals.…”
Section: Implications For Whole-body Locomotion and Comparative Biomechanicsmentioning
confidence: 56%
“…Aponeurosis may also play a role in limiting the effects of muscle mass in larger animals. We previously showed that larger muscles with greater mass store more energy in aponeurosis during cyclic contractions [64]. However, it is not yet clear what role this energy storage has in mitigating the effects of greater muscle mass, and if this role is altered with changes in aponeurosis properties with body size.…”
Section: Implications For Whole-body Locomotion and Comparative Biomechanicsmentioning
confidence: 99%